Thermal Conditions Relative to Atmospheric Circulation in the Christmas Period in Poland - Tomczyk, Arkadiusz M. (Quaestiones Geographicae, 2016)
The main objective of this article was to determine thermal conditions in the Christmas period and the impact of atmospheric circulation on their formation. The article is based on data on the mean daily air temperature for 16 stations in Poland for the 1966-2014 multiannual period. In this period, no statistically significant changes of air temperature were observed, neither in December, nor the Christmas period. The occurrence of averagely warmer holidays was associated with the inflow of maritime polar air masses from the western sector, while colder holidays occurred with the inflow of continental polar air masses from the eastern sector.